Endovascular treatment of portal hypertension and recurrent digestive hemorrhage secondary to arterioportal fistula syndrome: Late complication of penetrating abdominal trauma - Bertanha, Matheus [UNESP]; Moura, Regina [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Sobreira, Marcone Lima [UNESP]; Curtarelli, Arthur; Rosa, Felipe Damacena [UNESP]; Sembenelli, Marcelo [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2020)
The arterioportal fistula (APF) syndrome is a rare and reversible cause of pre-sinusoidal portal hypertension, caused by communication between a visceral artery and the portal venous system. Most patients are asymptomatic, but when they do develop symptoms, these are mainly related to gastrointestinal bleeding, ascites, congestive heart failure, and diarrhea. This therapeutic challenge presents a case of APF caused by a 20-year-old stabbing injury with unfavorable late clinical evolution, including significant malnutrition and severe digestive hemorrhages. The patient was treated using an endovascular procedure to occlude of the fistula.
Tratamento endovascular da hipertensão portal e da hemorragia digestiva recorrente e secundária à síndrome da fístula arterioportal: Complicação tardia de trauma abdominal penetrante
Keywords: Arteriovenous fistula; Endovascular procedures; Penetrating wounds; Portal hypertension; Vascular fistula